Helicobacter pylori healthy South Asians. Issue 6 (12th October 2020) - Kharel, Sanjeev; Bist, Anil; Shrestha, Suraj; Homagain, Sushan
Abstract : We aimed to estimate the pooled prevalence of Helicobacter pylori among asymptomatic South Asians based on available literature and highlight the importance of screening asymptomatic individuals and implementing preventive strategies for eradicating H. pylori . Electronic databases such as PubMed and Embase, a regional database of WHO South Asian Region, and gray literature sites were searched for relevant studies from 1983 to 5 May 2020. In addition, references of the included studies were thoroughly searched. The random‐effect model was used to calculate the pooled prevalence with a 95% confidence interval (CI) along with subgroup analysis. Analysis of 19 studies showed a pooled prevalence of 56.5%, ranging from 10.3 to 91.7%. In subgroup analysis by country, the highest prevalence rate was reported from Bangladesh (86.3%, 95% CI: 0.806–0.921), whereas the lowest prevalence was from Sri Lanka (10.3%, 95% CI: 0.072–0.135). No differences were found between males and females. Prevalence among children and adolescents was 65.3% (95% CI: 0.529–0.777), greater than adults, 56.9% (95% CI: 0.353–0.785). The prevalence rate showed a decreasing trend upon comparison of studies conducted before and after 2000. Our analysis reveals the high prevalence of H. pylori infection among asymptomatic healthy populations in South Asia, particularly in children and adolescents. Public health awareness and sanitation interventions, pure drinking water, and respective strategies on a policy level to eradicate H. pylori and additional extensive multicentric cohort studies are necessary. Abstract : Our article reports the high prevalence of Helicobacter pylori infection among the asymptomatic populations of South Asia, especially in children and adolescents compared to adults, but shows a decreasing trend. Public health interventions and timely screening are necessary to eradicate H. pylori and its complication.